SAE Technical Paper Series 2001
DOI: 10.4271/2001-01-0653
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Chemical Kinetic Modeling of Diesel Combustion with Oxygenated Fuels

Abstract: The influence of oxygenated hydrocarbons as additives to diesel fuels on ignition, NOx emissions and soot production has been examined using a detailed chemical kinetic reaction mechanism. N-heptane was used as a representative diesel fuel, and methanol, ethanol, dimethyl ether and dimethoxymethane were used as oxygenated fuel additives. It was found that addition of oxygenated hydrocarbons reduced NOx levels and reduced the production of soot precursors. When the overall oxygen content in the fuel reached app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 19 publications
5
66
0
Order By: Relevance
“…The PM emissions reduced from the value for conventional diesel fuel with no oxygen content to less than 2% of that value when the oxygen content of the fuel was 25-30% by mass. Curran et al [37] showed the influence of the oxygen content of fuels on the production of soot precursors using a detailed chemical kinetic model; the calculated values of the soot precursors decreased with increased oxygen content in the fuel. Therefore, it can be concluded that the soot formed in DME combustion should be almost zero at an oxygen content of 35% and no C-C bonds.…”
Section: Particulate Matter (Pm)mentioning
confidence: 99%
“…The PM emissions reduced from the value for conventional diesel fuel with no oxygen content to less than 2% of that value when the oxygen content of the fuel was 25-30% by mass. Curran et al [37] showed the influence of the oxygen content of fuels on the production of soot precursors using a detailed chemical kinetic model; the calculated values of the soot precursors decreased with increased oxygen content in the fuel. Therefore, it can be concluded that the soot formed in DME combustion should be almost zero at an oxygen content of 35% and no C-C bonds.…”
Section: Particulate Matter (Pm)mentioning
confidence: 99%
“…We generally follow the recommendations of Allara and Shaw [27]. The rate of addition of an H atom to an olefin is assumed to have an A-factor of 1.0 × 10 13 ; the activation is 1200 cal mol −1 if the H atom adds to the terminal end of the olefin double bond and approximately 2900 cal mol −1 if the addition is to the internal C atom. The rate for alkyl radical addition to olefins will have a lower A-factor and higher activation energy than for an addition of an H atom.…”
Section: Heptyl Radical Decompositionmentioning
confidence: 99%
“…In addition, a thorough reaction mechanism was developed for nheptane [10] which was significant because this fuel is a primary reference fuel for measuring knocking tendency in spark-ignition engines [11] and is a convenient representative diesel fuel for studies of ignition in diesel engines [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This tendency that larger amounts of CO are formed with increasing an ethanol fraction in fuel can be acceptable taking into consideration several reports by other researches. As Curran et al (2001) pointed out, C-O bond in the oxygenated compounds is very strong and remains permanently connected during combustion. According to the low temperature (800 K) oxidation of ethanol proposed by Mittal et al (2014), a path to form CO via formation of acetaldehyde or formaldehyde is one of the major reaction routes.…”
Section: Sem and Tem Images Of Synthesized Cntmentioning
confidence: 97%